Arsenic and lead induced free radical generation and their reversibility following chelation - Flora, S.J.S.; Flora, G.; Saxena, G.; Mishra, M. (Cellular and Molecular Biology, 2007)
Health hazards caused by heavy metals have become a great concern to the population. Lead and arsenic are one of the most important current global environmental toxicants. Their toxic manifestations are being considered caused primarily due to the imbalance between pro-oxidant and antioxidant homeostasis and also due to a high affinity of these metals for thiol groups on functional proteins. They also interfere with a number of other body functions and are known to affect central nervous system (CNS), hematopoietic system, liver and kidneys and produce serious disorders. They produce both acute and chronic poisoning, of which chronic poisoning is more dangerous as its very difficult to revert back to normal condition after chronic exposure to these insidious metals present in our life. Despite many years of research, we are still far from an effective treatment of chronic plumbism and arsenicosis. Current approved treatment lies in the administration of chelating agents that forms an insoluble complex with the metal and removes it. They have been used clinically as antidotes for treating acute and chronic poisoning. The most widely used chelating agents are calcium disodium ethylenediamine tetra acetic acid (CaNa2EDTA), D-penicillamine and British anti-lewisite (BAL). Meso 2,3 dimercaptosuccinic acid (DMSA), an analogue of BAL, has been tried successfully in animals as well as in humans. But it is unable to remove the metal from intracellular sites. Effective chelation therapy for intoxication by heavy metals depends on whether the chelating agents are able to reach the intracellular site where the heavy metal is firmly bound. One of the important approaches has been the use of combination therapy. This includes use of structurally different chelators or a combination of an adjuvant/ antioxidant/ herbal extracts and a chelator to provide better clinical/ biochemical recovery. A number of other strategies have been suggested to minimize the numerous problems. This article presents the recent development made in this area with possible directions for future research.